Tuning multicolor emission in AgNCs/Tm3+/Mn2+-doped fluorophosphate glasses - Fares, Hssen [UNESP]; Castro, Tarcio; Franco, Douglas Faza [UNESP]; Fucikova, Anna; da Silva, Robson R.; Valenta, Jan; Ribeiro, Sidney J.L. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier, 2020)
Herein we report the synthesis of highly-doped silver nanocluster in fluorophosphate glasses through the melting-quenching method in order to achieve sensitization with Tm3+ and Mn2+ ions. Blue and red emission belonging to Tm3+ (470 to 490 nm) and Mn2+ (550 to 750 nm) ions could be obtained via non-resonant excitation of Tm3+ and Mn2+. Slight decrease of the fluorescence decay times confirmed an energy transfer as a possible mechanism to explain the Tm3+ and Mn2+ emission. The composition of 5 mol% of AgNO3, 0.4 mol% of Tm2O3 and 0.2 mol% of MnF2 in our sample leads to distance between donor (silver nanoclusters) and acceptor (Tm3+-Mn2+) as short as 11 Å, which suggests that the main mechanism for blue and red emission from Tm3+ and Mn2+ is Förster Resonance Energy Transfer (FRET). The results presented here show that the studied material has potential application for multicolor generation as luminophore in white light emitting diodes (W-LED).
Keywords: Multicomponent fluorophosphate glasses; Sensitization lanthanide and metal ions; Silver nanoclusters; Visible emission